Erectile dysfunction - Hilz, Max-Josef; Wang, Ruihao; Vodušek, David B. (Springer International Publishing, 2023)
Male erectile dysfunction (ED) increases with age and afflicts 52% of the 40-70 year old men. Neurological, endocrine, vascular, inflammatory, metabolic diseases, traumata, tumorous causes, illicit or "recreational "drugs, numerous prescription drugs, and psychological or psychiatric causes may induce ED. Diabetes mellitus is a leading cause of ED. ED can be the first sign of diabetes but also of coronary artery disease and thus requires a careful evaluation. In addition to a detailed history, ED patients need a general physical examination and may need additional urological, internal medicine, endocrinological-andrological, psychiatric and neurological assessment. Phosphodiesterase type 5 inhibitors should only be prescribed to patients at low cardiovascular risk. Various side effects and strict contraindications, such as treatment with nitrates, NO-donors, or alpha-blockers, and several others must be considered. Other ED treatments include lifestyle changes, where appropriate testosterone replacement, psychosexual counselling, intracavernous or intra-urethral prostaglandin E1 applications, vacuum erection pumps, constrictions rings, penile arterial reconstructive surgery, and penile prosthesis.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cardiovascular disease; Diabetes mellitus; Erectile dysfunction; Impotence; Intracavernous prostaglandin E1 injections; Nitrates; Penile prosthesis; Phosphodiesterase type 5 inhibitors; Vacuum pumps